ABO and rhesus blood groups among blood donors in Kano, North-Western Nigeria - Chima, Onwuka; Mohammed, Tijjani; Kuliya-Gwarzo, Aisha; Alhaji, Samaila; Muhammad, Borodo; Kwaru, Aminu (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: The need for blood and blood products requires an efficient blood transfusion service. This study was undertaken to provide pro data on the distribution of ABO and Rhesus blood groups that would assist in planning and coordinating blood transfusion services for the cosmopolitan city of Kano.Materials and Methods: A total of 5000 consecutive blood donor samples were grouped for ABO and Rhesus ‘D’ antigen by tile and tube methods at Aminu Kano Teaching Hospital (AKTH) over a one-year period.Results: Blood group O had the highest prevalence of 2860 (57.2%) followed by blood group B of 1035 (20.7%), then A of 1025 (20.5%) and the lowest being AB of 80 (1.6%). A total of 4741 (94.8%) of the study group were Rhesus ‘D’ positive while 259 (5.2%) were Rhesus ‘D’ negative.Conclusion: The ABO blood group had blood group O as the most prevalent blood group in the study population while the lowest was AB. The Rhesus blood group positive was 94.8% while Rhesus negative blood group was 5.2%.
Keywords: ABO; blood group; Kano; Nigeria; Rhesus